Plasma C1q/TNF-Related Protein-9 Levels Are Associated with Atherosclerosis in Patients with Type 2 Diabetes without Renal Dysfunction - Mariko Asada; Tomoaki Morioka; Yuko Yamazaki; Yoshinori Kakutani; Reina Kawarabayashi; Koka Motoyama; Katsuhito Mori; Shinya Fukumoto; Atsushi Shioi; Tetsuo Shoji; Masanori Emoto; Masaaki Inaba (Journal of Diabetes Research)
Aim. C1q/tumor necrosis factor-related protein-9 (CTRP9), a paralog of adiponectin, is expressed in adipose tissue. CTRP9 exerts protective effects against obesity and atherosclerosis in rodents. We investigated the association between plasma CTRP9 levels and atherosclerosis in patients with type 2 diabetes. Methods. We included 419 patients with type 2 diabetes, 161 of whom had chronic kidney disease (CKD). Fasting plasma CTRP9 and total adiponectin levels were measured with enzyme-linked immunosorbent assay. The intima-media thickness (IMT) of the common carotid artery was measured with ultrasonography. Results. Plasma CTRP9 levels were higher in the CKD group than in the non-CKD group. Plasma CTRP9 levels were positively correlated with carotid IMT in the non-CKD group. Multivariate analyses revealed that plasma CTRP9 levels were positively associated with carotid IMT in the non-CKD group, independent of age, sex, body mass index, adiponectin, and other cardiovascular risk factors. However, plasma CTRP9 levels were not associated with carotid IMT in the CKD group. Conclusion. Plasma CTRP9 levels are associated with atherosclerosis in diabetic patients without CKD, independently of obesity, adiponectin, and traditional cardiovascular risk factors. This study indicates a potential role of CTRP9 in atherosclerosis progression in human type 2 diabetes.